Anterior Skull Base Outcomes and Complications: A Propensity Score–Matched Evaluation of Age and Frailty as Measured by mFI-5 from the ACS-NSQIP Database - Bauer, Sawyer; Findlay, Matt; Khan, Majid; Alexander, Hepzibha; Lucke-Wold, Brandon; Hamrick, Forrest; Hunsaker, Josh; Karsy, Michael (Indian Journal of Neurosurgery, 2023)
Background Frailty is increasingly recognized as a predictor of surgical outcomes; however, its utility in anterior cranial fossa (ACF) surgery remains unclear. We analyzed whether age and frailty are independent predictors of outcomes after ACF surgery using a retrospective cohort study.Methods The American College of Surgeons National Surgical Quality Improvement Program database was queried, by Current Procedural Terminology codes, for ACF procedures in 2005 to 2020. Cases included open approaches, endoscopic approaches, and all tumor types except for pituitary adenoma. A propensity score–matched data set was analyzed via multiple logistic regression.Results Unmatched multivariate analysis of ACF cases demonstrated that severe frailty (modified 5-item frailty index [mFI-5] ≥ 3) was independently associated with having any (odds ratio [OR] = 3.67) and minor (OR = 5.00) complications (both p < 0.001). Analysis of individual mFI-5 components demonstrated poor functional status was significantly associated with any (OR = 3.39), major (OR = 3.59), and minor (OR = 3.14) complications (all p < 0.001). After propensity score matching, only age was modestly impactful on minor complications (OR = 1.02) and extended length of stay (eLOS) (OR = 1.02) (p < 0.001). Frailty did not maintain its predictive ability after matching. Nonindependent functional status, as a subcomponent of mFI maintained significant predictive ability for any (OR = 4.94), major (OR = 4.68), and minor (OR = 4.80) complications and eLOS (OR = 2.92) (all p < 0.001).Conclusion After propensity score matching, age demonstrated a greater ability to predict postoperative complications in ACF surgery than frailty. Rather than age or frailty, functional status served as a better outcome predictor and potential guide for patient counseling. Further validation of these findings in multicenter or disease-specific studies is warranted as well as aims to preoperatively improve functional status in ACF surgery.
Keywords: age; anterior cranial fossa; anterior skull base; complications; frailty; mFI-5; modified 5-item frailty index; National Surgical Quality Improvement Program; neurosurgery; NSQIP; propensity score matching